Unmet patient needs in monocarboxylate transporter 8 (MCT8) deficiency: a review - Bauer, Andrew J.; Auble, Bethany; Clark, Amy L.; Hu, Tina Y.; Isaza, Amber; McNerney, Kyle P.; Metzger, Daniel L.; Nicol, Lindsey; Pierce, Samuel R.; Sidlow, Richard (Frontiers in Pediatrics, 2024)
Monocarboxylate transporter 8 (MCT8) deficiency is a rare, X-linked disorder arising from mutations in the SLC16A2 gene and resulting from dysfunctional thyroid hormone transport. This disorder is characterized by profound neurodevelopmental delay and motor disability due to a lack of thyroid hormone in the brain, and coexisting endocrinological symptoms, due to chronic thyrotoxicosis, resulting from elevated thyroid hormone outside the central nervous system (CNS). In February 2024, we reviewed the published literature to identify relevant articles reporting on the current unmet needs of patients with MCT8 deficiency. There are several main challenges in the diagnosis and treatment of MCT8 deficiency, with decreased awareness and recognition of MCT8 deficiency among healthcare professionals (HCPs) associated with misdiagnosis and delays in diagnosis. Diagnostic delay may also be attributed to other factors, including the complex symptomology of MCT8 deficiency only becoming apparent several months after birth and pathognomonic serum triiodothyronine (T3) testing not being routinely performed. For patients with MCT8 deficiency, multidisciplinary team care is vital to optimize the support provided to patients and their caregivers. Although there are currently no approved treatments specifically for MCT8 deficiency, earlier identification and diagnosis of this disorder enables earlier access to supportive care and developing treatments focused on improving outcomes and quality of life for both patients and caregivers.